APLIKASI INTERVENSI NYERI PADA ARTRITIS SENDI FASET LUMBALIS - Sekplin A. S. Sekeon; Sandi Kumala (Jurnal Sinaps, 2019)
Lumbal faset joint pain is a common cause of low back pain. The incidence is increasing with age. The prevalence of faset joint pain is 27-40% of chronic low back pain. Faset joint osteoarthritis is the most common etiology of faset pain. History taking and physical examination can suspect a faset pain but cannot determine the cause of pain originating from the faset joint. Therefore, the diagnosis of faset joint pain can also be confirmed if there is improvement after faset joint injection (FJI). FJI is a pain intervention management by injecting local anesthetics and steroids in the faset joints under fluoroscopy or ultrasonography guided. This treatment is relatively has relatively minimal side effects compared to other intraspinal injection techniques because it only injects directly into the faset joint through the paraspinal muscles.